Haemato-biochemical profiles, body condition and FAMACHA scores at various ages and their interrelations in Surti goats (Indian Journal of Animal Production and Management, 2016)
The effect of age on haemato-biochemical parameters, BCS and FAMACHA scoring were studied in  traditionally reared Surti goats in south Gujarat. Total 240 adult goats, 72 yearlings (1 year to 1st kidding)  and 48 kids (Upto 6 month age) were selected for study. All were monitored for FAMACHA and BCS  simultaneously with blood samples collection. The PCV was measured by micro-haematocrit method  and biochemical parameters were measured on biochemical analyzer. BCS and PCV were significantly  higher in kids and yearlings than adult goats. The younger goats were also having low FAMACHA scoring.  Blood glucose, cholesterol, total protein, albumin, A:G ratio, urea, creatinine, calcium, magnesium, ALT  and AST did not vary significantly between kids, yearlings or adults Surti goats, whereas, triglycerides and  phosphorus were found significantly higher in younger goats and globulin was significantly higher in adult  goats. BCS and PCV have significantly positive whereas FAMACHA has significant negative correlations  with most of blood parameters.
Keywords: Age; BCS; FAMACHA; Goats; Haemato-biochemical; PCV